Seleksi Kandidat Balloon Mitral Valvuloplasty pada Stenosis Mitral Rematik - Amiliana M Soesanto (The Indonesian Heart Association, 2013)
Balloon Mitral Valvulotomy (BMV), sometimes also referred to as Percutaneous Transcatheter Mitral Commissurotomy (PTMC) is becoming a common treatment option for patients with mitral stenosis. Compared to surgical valvotomy, it has less procedural risk, shorter hospital stay and comparable outcome. However, that good result can only be achieved in selected good candidates. This article will give a highlight of some consideration to choose a good candidate for BMV mostly evaluated by echocardiography.